Quiddity and Practical Sentences Understanding Potency Functioning - Muhammad Ali Nouri (آموزه‌‌های فلسفه اسلامي)
There have been several views by Muslim scholars on the quiddity of theoretical and practical reason and how they function in the understanding of practical sentences. One view considers theoretical reason; the understanding of the basis of all general theories, including theoretical and practical reasons, and practical reason considers the principle of partial practical and also determinants of action (Ibn Sian’s view). The other view considers the theoretical reason only as the understanding of the theoretical sentences and considers the practical reason as the understanding of the general and partial practical sentences and considers as the instigator the act’s doing. (Al-Tusi’s view and al-Ghazali in Maqasid al-Falasifa). The third view considers theoretical reason as both the theoretical and the general and partial practical sentences, and considers the practical reason to be the sole agent of action and the temptation of it. (Bahmanyar’s view, Qutb al-Din al-Razi, and al-Ghazali’s in Miar al-Elm). The present article, by explaining the angles of these three perspectives and analyzing the speeches in this regard, argues that the right view is the second view and that the practical reason is two kinds. One deals with generalities, which is the equivalent of theoretical reason, but understands general practical understanding. Another deals with details that understand both the practical details and how to do and deal with them.